Pengembangan Media Pembelajaran Berbasis Android “Ispring Suite” Untuk Keterampilan Membaca Di Madrasah Ibtidaiyyah - Risa Safitri; Amrini Shofiyani (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
This study aims to develop Arabic learning media based on Android iSpring Suite for the reading skills of fourth graders at Madarasah ibtidayyah of Jombang. The research uses the R&D method, the development model uses ADDIE, there are five stages, namely analysis, design, development, implementation and evaluation. Analysis using a Likert scale, data collection techniques using observation, interviews and questionnaires. Based on data analysis of 30 students in the fourth graders at Madarasah ibtidayyah of Jombang, it was found that up to 91% (very good) with this learning media making participants enthusiastic and interested in using innovative and educative means in overcoming difficulties and boredom them to learn.